2012
DOI: 10.4236/ajps.2012.310170
|View full text |Cite
|
Sign up to set email alerts
|

Antinutritive Compounds in Twelve <i>Camelina sativa </i>Genotypes

Abstract: <i>Camelina sativa</i> is an oilseed crop becoming important in North America and Europe for biodiesel production. The use of <i>Camelina</i> flours in animal diet may be limited by antinutritive compounds. The content of glucosinolates, phytic acid, sinapine and condensed tannins was evaluated in twelve accessions of <i>Camelina sativa</i>. All compounds showed significant differences among genotypes. Only the concentration of glucosinolates in the flour deserves attention,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 23 publications
7
56
2
Order By: Relevance
“…In a previous work [16], a negative correlation was found between total GSLs and sinapine analyzing only 12 accessions. Table 3 shows that, with a greater number of accessions which makes the test more reliable, such a correlation is not verified (both on total and on individual GSLs).…”
Section: Correlations Between Gsls and Sinapine In Camelina Accessionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous work [16], a negative correlation was found between total GSLs and sinapine analyzing only 12 accessions. Table 3 shows that, with a greater number of accessions which makes the test more reliable, such a correlation is not verified (both on total and on individual GSLs).…”
Section: Correlations Between Gsls and Sinapine In Camelina Accessionsmentioning
confidence: 99%
“…GSL extraction and assay basically follows the official HPLC method (ISO 9167-1) but adapted to camelina GSLs from Russo and Reggiani [16]. GSLs were extracted with 70% hot ethanol overnight and the sample centrifuged for 15 min Desulfo-GSLs were separated by HPLC according to Russo et al [18].…”
Section: Extraction and Separation Of Gslsmentioning
confidence: 99%
“…Recently, the industrial interest on camelina has rapidly grown (Putnam et al, 1993) due to its unique FA composition and sound attractive applications such as drying oil with environmentally safe painting and coating applications similarly to linseed oil (Luehs and Friedt, 1993;Russo and Reggiani, 2012). Moreover, unlike the majority of wild-type Brassicaceae, camelina shows a rather low glucosinolate content (Lange et al, 1995), which makes the possible utilization of meal much easier.…”
Section: Introductionmentioning
confidence: 99%
“…On the other side of GSLs, the isothiocyanates, active metabolites of GSLs from other brassica crops were explored for their anticancer properties and, hence, CM can also be examined for other related activities (Talalay and Zhang, 1996). Glucosinolates are considered bitter to humans (Mithen et al, 2000;Russo and Reggiani, 2012b), chickens (Pekel et al, 2009), fish (Morais et al, 2012) and pigs (Eidhin et al, 2003) and has been found to reduce feed intake in a dose-dependent manner. Large doses of thiocyanate, a glucosinolate metabolite affects iodine transport to thyroid (Schone et al, 1990).…”
Section: Antinutritive Compounds In Camelina Seedmentioning
confidence: 99%